Microbial community succession during tobacco fermentation reveals a flavor-improving mechanism - Zhu, Jingjing; Wang, Jitao; An, Zichao; Shen, Chen; Dong, Hongxu; Wang, Haojun; Peng, Zhenxing; Yang, Bo; Liu, Juanjuan; Wang, Xiaojie; Fang, Zemin (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionFlue-cured tobacco (FCT) requires fermentation to increase quality, with microorganisms playing a key role. However, microbial succession and functions during long-term fermentation remain unclear. Artificial microbial fermentation, which is more controllable and efficient, focuses on mining functional strains to optimize the process.MethodsIn this study, the microbial community structure and function of FCT fermentated for 0–4 years were analyzed, and the changes of metabolites in tobacco leaves in different years were analyzed. Functional microorganisms were screened, and their potential for application in FCT fermentation was evaluated.ResultsThe results revealed that the FCT aging process was typified by the metabolic, transformative, and synthetic processes of alkaloids, their derivatives, and benzene ring compounds. Microbial succession leads to changes in metabolites, with Escherichia, Bacillus, Enterococcus, Alternaria, Vibrio, and Halomonas playing crucial roles in the breakdown of fundamental substances during the initial year of FCT fermentation. Bacillus, one of the dominant and highly active genus of the microbial community on the surface of tobacco leaves, exhibits significantly increased abundance during FCT fermentation and improves the aroma and flavor of tobacco leaves by participating in aromatic amino acid metabolism. After 15 days of treatment with a combination of four Bacillus strains (Bacillus altitudinis YS193, Bacillus pumilus YH186, Bacillus tequilensis YS154, and Bacillus velezensis YS157), the sugar‒nicotine ratio of FCT was effectively optimized, the sensory flavor was enhanced, and the levels of volatile compounds associated with the aromatic amino acid metabolic pathway were significantly increased.DiscussionThis study reveals the critical role of microbial succession in FCT fermentation and demonstrates that targeted inoculation of functional Bacillus strains can significantly improve tobacco quality by modulating key metabolic pathways, providing a scientific basis for artificial microbial fermentation in tobacco processing.